2016
DOI: 10.1136/bmjsem-2016-000124
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and risk factors of depression during and after the football career of elite female players

Abstract: BackgroundThe mental health of elite athletes has received increasing attention in recent years, but no study has evaluated the career–time prevalence of depression, and very few have analysed risk factors of mental health problems during or after the career.Methods157 (response rate 64.1%) female players who played in the German First League answered an anonymous online survey on details of their football career, stressful and helpful conditions, depression and need of psychotherapeutic support during and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 40 publications
4
67
3
3
Order By: Relevance
“…In contrast to Prinz et al 20 and Junge and Feddermann-Demont10 but in agreement with Gouttebarge et al ,34 no effect of playing position on the prevalence of depression symptoms was observed in the present study. In the present study injured and uninjured players had similar depression and generalised anxiety rates.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast to Prinz et al 20 and Junge and Feddermann-Demont10 but in agreement with Gouttebarge et al ,34 no effect of playing position on the prevalence of depression symptoms was observed in the present study. In the present study injured and uninjured players had similar depression and generalised anxiety rates.…”
Section: Discussionsupporting
confidence: 90%
“…Players with the highest match experience had lower average depression and anxiety rates, and this extends previous reports by Prinz et al 20 for former elite female football players, and by Junge and Feddermann10 for active elite male and female football players. Multivariate regression analysis showed that match experience was a predictor for depression and generalised anxiety symptoms independent of level of play.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This might be explained because during their sport career, elite athletes are exposed to generic factors such as adverse life events but also to sport-specific stressors 6 45. For instance, a greater overall risk of mental health symptoms and disorders might be experienced by elite athletes with severe musculoskeletal injuries, multiple surgeries, decreased sport performance or maladaptive perfectionism 24 43 46–50. Prevalence of alcohol misuse calculated in our meta-analyses was similar among current and former elite athletes, namely 19% vs 21%, respectively.…”
Section: Discussionmentioning
confidence: 70%